2022
DOI: 10.2196/32220
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Flexible Assertive Community Treatment (FACT) Model in Norway: eHealth Assessment Study

Abstract: Background Flexible Assertive Community Treatment (FACT) is a model for treatment of long-term severe mental disorders. This method has become more widespread in Norway. Objective The objective of our study was to examine how the implementation of FACT teams in Norway has been affected by eHealth policy, infrastructure, and regulations. Another objective was to examine existing literature on eHealth interventions and challenges within FACT teams. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Studies have shown that ACT ( 14 ) and FACT ( 13 ) teams can mitigate the problem of long travel distances using digital meetings, including in situations of crisis management ( 14 ). Both the present study and another Norwegian study ( 74 ), described how virtual tools increased in the FACT teams because to the COVID-19 pandemic, and one might state that the pandemic therefore contributed in this adaption, possibly also in urban regions. However, both studies showed that digital solutions do not work in all situations; this modification is not always a suitable solution in patient care.…”
Section: Discussionsupporting
confidence: 53%
“…Studies have shown that ACT ( 14 ) and FACT ( 13 ) teams can mitigate the problem of long travel distances using digital meetings, including in situations of crisis management ( 14 ). Both the present study and another Norwegian study ( 74 ), described how virtual tools increased in the FACT teams because to the COVID-19 pandemic, and one might state that the pandemic therefore contributed in this adaption, possibly also in urban regions. However, both studies showed that digital solutions do not work in all situations; this modification is not always a suitable solution in patient care.…”
Section: Discussionsupporting
confidence: 53%
“…During the semistructured interviews, the team leaders and team coordinators in all five teams were interviewed one-to-one using an interview guide. The questions in the interview guide, provided in Textbox 1, were based on previous knowledge of the use of ICT tools in Norwegian FACT teams [9]. The interviews varied in length from 30 to 60 minutes.…”
Section: Data Collection and Designmentioning
confidence: 99%
“…However, there are several different EHR systems in use in primary care. Since most FACT teams are organized as a cooperation between specialist care and one or more municipalities, this leads to several different EHR systems being available for most teams [9]. FACT teams have daily meetings, where they go through their list of patients who require intensive follow-up to keep all team members updated on the patient's status and further treatment plans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HCPs are facing challenges in delivering palliative care, including the introduction of new digital health technologies, organizational challenges, fragmented health services, staff shortages, and emotional fatigue (Bessen et al, 2019 ; Bønes et al, 2022a ; Melby & Håland, 2021 ). There is a global shortage amounting to millions of healthcare professionals (Liu et al, 2017 ) and a growing and ageing population (United Nations, 2019 ), with the older population having comorbidities (Guidelines, Network AI, 2020 ; Siemens et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%